Perlukah Etika Bisnis? - Chang, William (MABIS, 2011)
The application of business ethics in modern societies shows us the importance of ethical values, such as honesty, justice, responsibility and mutual-understanding in business world. Stakeholders approach on business ethics reminds us the need of good collaboration of those who get involved in business. The realization of business ethics should start with the reformation of human beingsâ mind sets, way of thinking and style of life. So, how can we internalize and implant the values of business ethics in Indonesia?Key words: business ethics, ethical values, structure of human acts, honesty, social justice,